Government publications relating to Nigeria, 1862-1960 (Government publications relating to Africa in microform., 1975)
Group 1, Lagos Colony and Protectorate, 1862-1905 (19 reels).--Group 2, Niger Coast (Oil Rivers) Protectorate, 1891-1899 (39 reels).--Group 3, Nigeria Colony and Protectorate, 1914-1939 (115 reels).--Group 4, Nigeria Colony and Protectorate, 1940-1959 (42 reels)